Effects of early interventions focused on the family in the development of children born preterm and/or at social risk: a meta‐analysis - Rachel de Carvalho Ferreira; Claudia Regina Lindgren Alves; Marina Aguiar Pires Guimarães; Kênia Kiefer Parreiras de Menezes; Lívia de Castro Magalhães (Brazilian Society of Pediatrics, 2020)
Objective: To verify whether early intervention focused on the family improves the cognitive, motor, and language development of children born preterm and/or at social risk in the first 3 years of life. Source of data: Meta‐analysis of clinical trials published between 2008 and 2018, in the following databases: CINAHL, MEDLINE - PubMed, MEDLINE - BVS, LILACS - BVS, IBECS - BVS, PEDro and Cochrane Reviews. Experimental studies on early interventions focused on the family, whose target groups were children born preterm and/or at social risk, with assessment of cognitive and/or motor and/or language development up to 3 years were included. The studies were rated using the PEDro Scale. Data synthesis: Twelve studies were included from a total of 3378 articles. Early intervention focused on the family contributed to the development of the cognitive (Standardized Mean Difference - SMD = 0.48, 95% CI: 0.34-0.61) and motor (SMD = 0.76, 95% CI: 0.55-0.96) domains of preterm infants. Regarding cognitive development, performance improvement was observed at 12, 24 and 36 months, while in the motor domain, the effect was observed only at 12 months in preterm infants. There was no benefit of the intervention in the cognitive, motor, and language outcomes of children with the social risk factor associated to biological risk. Conclusion: Early intervention focused on the family has a positive effect on the cognition of preterm infants. The effect on motor development was lower, possibly due to the emphasis on interventions in family-child interaction. The effect of interventions on the development of children at social risk and on the language domain was inconclusive, due to the scarcity of studies in the area. Resumo: Objetivo: Verificar se a intervenção precoce com foco na família melhora o desenvolvimento cognitivo, motor e a linguagem de crianças nascidas prematuras e/ou em risco social nos primeiros três anos de vida. Fontes de dados: Metanálise de ensaios clínicos publicados entre 2008 a 2018, nas bases de dados CINAHL, Medline - Pubmed, Medline - BVS, Lilacs - BVS, IBECS - BVS, PEDro e Cochrane/Reviews. Foram incluídos estudos experimentais de intervenção precoce com foco na família cujo público‐alvo eram prematuros e/ou crianças em risco social com avaliação do desenvolvimento cognitivo e/ou motor e/ou linguagem até os três anos. Os artigos foram pontuados pela Escala PEDro. Síntese dos dados: Do total de 3378 artigos, 12 estudos foram incluídos. A intervenção precoce com foco na família contribuiu para o desenvolvimento dos domínios cognição (DMP = 0,48; 95%IC: 0,34‐0,61) e motor (DMP = 0,76; 95% IC: 0,55‐0,96) de prematuros. Na cognição, a melhora do desempenho foi observada aos 12, 24 e 36 meses, enquanto no domínio motor, o efeito foi observado apenas aos 12 meses nos prematuros. Não houve benefício da intervenção nos desfechos cognitivo, motor e linguagem de crianças com fator de risco social associado ao biológico. Conclusão: Intervenção com foco na família tem efeito positivo sobre a cognição de crianças prematuras. O efeito no desenvolvimento motor foi menor, possivelmente devido à ênfase das intervenções na interação família‐criança. O efeito das intervenções sobre o desenvolvimento de crianças em risco social e no domínio da linguagem foram inconclusivos, devido à escassez de estudos na área. Keywords: Early intervention (education), Parents, Child development, Infant, Premature newborn, Risk factors, Palavras‐chave: Intervenção precoce (educação), Pais, Desenvolvimento infantil, Bebê, Recém‐nascido prematuro, Fatores de risco